Intricately carved mouldings of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
The east-facing elevation of the Chaunsath Yogini Temple is better preserved than other parts. In elevation, the temple has several basal mouldings. All these mouldings are profusely carved with intricate designs. Above this is the jangha (wall) and the remains of the shikhara (superstructure) of the temple. The kumbha (pot) moulding from the vedibandha (basal mouldings) of this temple is the most ornate, with leafy patterns on its edges and deities within framed niches on the front faces.